Peran Organisasi Kemasyarakatan Dalam Meningkatkan Partisipasi Politik Masyarakat Tionghoa di Kota Medan - Faraidiany, Maghfira; putri, annisa; mukhrijal, mukhrijal (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2023)
This study aims to explain the role of community organizations in increasing the political participation of the Chinese community in Medan City. This study uses a qualitative approach with a case study strategy that is descriptive and analytical. Research data processing uses the triangulation method to ensure reliability, validity, and generability. The results showed that the INTI Association as one of the largest Chinese community organizations in Medan City was able to increase the participation of the Chinese community. First; The Chinese community in Medan City has actively participated in the world of politics as indicated by the many members of the association who have nominated themselves to become members of the legislature. Second, the negative value of the role of community organizations is used as a tool to get the votes of community organization members. This is because there is support or encouragement from members of the organization who will nominate themselves so that votes are needed to win political contestation.